Deviant truth-values algebras and deviant classes of general non-deterministic predicates 14 Software environment and tools - Shkilniak, O.S. (PROBLEMS IN PROGRAMMING, 2019)
In this paper we study new classes of program-oriented logical formalisms – logics of general non-deterministic (GND) predicates. These logics reflect such properties of programs as nondeterminism, partiality, and non-fixed arity. GND-predicates can be modeled as 7-valued total deterministic (TD7) predicates. The main attention is paid to algebras of truth values (TV-algebras) of TD7-predicates. The set of truth values TV7 = {T, F, T#, F#, #,  TF, TF#} defines TV-algebrа ATV7 = (TV7,  {Ø*, Ú*}). There 20 subalgebras of ATV7 exist, and each of them induces a corresponding algebra of GND-predicates. At the same time there is a very large number of 7-valued logics so a lot of TV7 subsets are not closed under Ø* or Ú* and do not form subalgebras of ATV7. We call such subsets with the corresponding classes of GND-predicates deviant, they are not closed under logical connectives of GND-predicates. In order for deviant TV Í TV7 to form an algebra we need to modify Ø* or Ú*. Modifications can be made in a large number of ways. Modification of Ø* leads to specific non-classical logics and lies outside the scope of this paper. Modifications of Ú* satisfying the TFC condition of predicate algebras logical connectives correctness are the most important, otherwise we obtain deviant TV-algebra which does not induce an algebra of GND-predicates. For all TV7 subsets we study the possibility of Ú* modification with TFC condition. Such modification induces corresponding classes of GND-predicates. We describe “natural” modifications of Ú* without TFC condition obtaining a number of deviant TV-algebras. There are no modifications with TFC condition for deviant sets {#, TF, TF#}, {TF, #}, {TF#, #}, so for them we specify “relatively natural” deviant TV-algebras.Problems in programming 2019; 1: 14-26